EMPOWERING WOMEN THROUGH THE CREATIVE WOMEN'S GROUP (KWK) PROGRAM IN UJONG TANOH DARAT VILLAGE - Siti Aminah Rahman; Anggun Triana; Fitriani; Rifaldi; Asmarida; M.Raja Tuleut; Mutiara Hasnah; Nadya Eka Syahrani; Nurul Lisa; Putri Amanda; Primarini Anggra; Resa Nazwa; Sasrianda Waruwu; Virna Rahma Qeysha; Yuwen Serly (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The dense population in Indonesia has caused poverty and unemployment problems everywhere, including in Ujong Tanoh Darat village. The problems of poverty and unemployment have increased from year to year, this has become a social problem that can cause inequality in society. One of the symptoms of poverty is low human resources caused by the lack of knowledge, especially in Ujong Tanoh Darat village. Another problem in this village is poor environmental sanitation as indicated by the rampant garbage in the environment in the village. Good waste management starting from managing inorganic waste into handicrafts (KAHASTA) and managing organic waste into fertilizer (Ecoharvest and Biowaste) is a solution to overcome these problems. This program aims to evaluate the effectiveness of assistance provided to women's groups in developing their skills, creativity, and productivity. The methods used include assistance and empowerment with the Grounded Theory approach, Focus Group Discussion, and training in utilizing local potential. The implementation of the program includes making handicrafts, Ecobrick gardens, and training in waste management and product marketing through social media.